Fast Response Ammonia Gas Sensor Based on SnO2 Nanoporous Synthesized By the Simple Heat-Up Method - Chaiyo, Pitchanunt (Science Essence Journal, 2023)
This paper investigated the electrical and gas-sensing properties of SnO2 nanoporous synthesized via the simple heat-up method. The I-V characteristics of the SnO2 nanoporous revealed Ohmic contact materials. The SnO2 nanoporous sensor was tested upon exposure to 50 ppm ammonia gas at 250 °C. It showed an immediate response to ammonia with a recovery time of 200 s in the first cycle. Additionally, the SnO2 nanoporous sensor was tested for its response to ammonia gas at concentrations ranging from 10 ppm to 90 ppm at a temperature of 250 °C. The results indicated that the SnO2 nanoporous sensor responded to ammonia gas at low concentrations, even as low as 10 ppm. Furthermore, the relative response value of the SnO2 nanoporous sensor demonstrated an increase in relative response value with increasing NH3 concentration.